Pioglitazone and Risk for Bone Fracture: Safety Data From a Randomized Clinical Trial - Viscoli, Catherine M. (J Clin Endocrinol Metab, 2016)
CONTEXT: Pioglitazone reduces cardiovascular risk in nondiabetic patients after an ischemic stroke or transient ischemic attack (TIA) but is associated with increased risk for bone fracture. OBJECTIVE: To characterize fractures associated with pioglitazone by location, mechanism, severity, timing, and sex. DESIGN, SETTING, AND PATIENTS: Patients were 3876 nondiabetic participants in the Insulin Resistance Intervention after Stroke trial randomized to pioglitazone or placebo and followed for a median of 4.8 years. Fractures were identified through quarterly interviews. RESULTS: At 5 years, the increment in fracture risk between pioglitazone and placebo groups was 4.9% [13.6% vs 8.8%; hazard ratio (HR), 1.53; 95% confidence interval (CI), 1.24 to 1.89). In each group, ∼80% of fractures were low energy (i.e., resulted from fall) and 45% were serious (i.e., required surgery or hospitalization). For serious fractures most likely to be related to pioglitazone (low energy, nonpathological), the risk increment was 1.6% (4.7% vs 3.1%; HR, 1.47; 95% CI, 1.03 to 2.09). Increased risk for any fracture was observed in men (9.4% vs 5.2%; HR, 1.83; 95% CI, 1.36 to 2.48) and women (14.9% vs 11.6%; HR, 1.32; 95% CI, 0.98 to 1.78; interaction P = 0.13). CONCLUSIONS: Fractures affected 8.8% of placebo-treated patients within 5 years after an ischemic stroke or TIA. Pioglitazone increased the absolute fracture risk by 1.6% to 4.9% and the relative risk by 47% to 60%, depending on fracture classification. Our analysis suggests that treatments to improve bone health and prevent falls may help optimize the risk/benefit ratio for pioglitazone.